Pengaruh Strategic Experiential Marketing/SEMs terhadap Kepuasan Pelanggan (The Effect of Strategic Experiential Marketing/SEMs on Customer Satisfaction) - Arif Sudaryana; Rahayu Nurfanovita; Suhartapa Suhartapa (STIE Malangkucecwara, 2022)
This study aims to see how the influence of strategic experiential marketing/SEMs namely sense, feel, think, act, and relationship on customer satisfaction. The study was conducted in a location in the Special Region of Yogyakarta in 2020, with a population of all customers of Matahari Department Store Yogyakarta.The number of samples used is 120 respondents. In taking the sample used purposive sampling method. To analyze the data, the tool used in this research is multiple linear regression analysis.The data analysis tool used in this research is multiple linear regression analysis. The conclusion of the research shows that there is a significant influence either partially or simultaneously between experiential marketing variables on customer satisfaction.